ATRIAL FIBRILLATION ASSOCIATED WITH MYOCARDIAL INFARCTION OF DIFFERENT LOCALIZATIONS - R. Bhattarai; S. A. Sayganov; E. V. Trofimova (Столичная издательская компания, 2015)
Aim. To specify the mechanism of atrial fibrillation (AF) development and to evaluate the function of left atrium after restoration of sinus rhythm in patients with AF and acute myocardial infarction (MI) without significant reduction in left ventricular systolic function. Material and methods. 52 patients with MI were enrolled into the study and divided into 2 groups. The first group included 29 patients with inferior MI, the second one - 23 patients with anterior MI. All patients underwent percutaneous intervention within first 24 hours after the onset of MI symptoms. Time and triggering factors of AF symptoms onset, its duration, the size of the heart chambers and time of left atrium function recovery were evaluated. Results. In patients with anterior MI AF developed later than in those with inferior MI (on day 2 in 12 patients and on day 3 - in 11 patients with anterior MI versus on day 1 in 25 patients and on day 2 - in 4 patients with inferior MI, p<0.05). Besides, in case of inferior MI the AF paroxysms were less persistent. The average duration in the first and second groups was 5.3±4.8 vs 42.3±12.1 hours, respectively; p<0.0001. There were also differences in the triggering factors of AF paroxysms. So, only 5 patients with inferior MI had congestive heart failure class KIllip II or higher, while in the second group it was present in 20 patients; p<0.0001. AF paroxysms in patients with anterior MI were accompanied by severe hemodynamic disorders and significantly worsened the prognosis. The assessment of left atrium function showed that it's often not impaired in inferior MI after sinus rhythm restoration (we observed normal peak A on the Doppler transmitral flow image in 25 patients). In case of anterior MI the effective atrial systole was absent for at least 7 days in 13 patients; p<0.005. Conclusion. AF has less favorable course in anterior MI. In this category of patients AF paroxysms are followed by hemodynamic disorders, and after the restoration of sinus rhythm the majority of patients has consistently impaired mechanical function of the left atrium, which is related to an increased risk of thromboembolic complications.